Intercultural aspects of online communication a comparison of mandarin‐speaking, US, Egyptian and German user preferences - Seidenspinner, Margarete; Theuner, Gabriele (Journal of Business Economics and Management, 2007)
This paper sums up the results of a survey conducted with four samples of website users, i.e. young urban academics from the PR of China, the United States, Egypt and Germany. The survey analyses the ways in which users from such distinctly dissimilar cultural environments view websites. The websites researched are those of global operators that either offer international services, high price utility items or technologically advanced products. The results gained in the course of this research project demonstrate how the targeted users’ cultural environments may impact on their preferred navigation tools, their perceived quality of web designs and on the perception and processing of the information provided online. A brief overview of the consequences which derive from this culture‐bound user behaviour for corporate communication policies conclude this paper.First Published Online: 14 Oct 2010